EXTRACURRICULAR CLASSES FOR STUDENTS IN ACADEMIC SUBJECTS (ORGANIZATIONAL-PEDAGOGICAL ASPECTS) - V I Kazarenkov; Juri Prokop; T B Kazarenkova (Peoples' Friendship University of Russia (RUDN University), 2015)
The article presents the pedagogical foundations of organizing the extracurricular activities of the students in various academic disciplines. The content of the article reflects the situation characterizing the importance of the purposeful development of these activities for the successful socialization, professionalization and self-realization in the system of university education. The actualization of extracurricular work is determined by the socio-economic changes taking place in the Russian state and society, and thus in higher education. Drawing on the analysis of the scientific literature and the state of practice of the specialist training in high school we have identified the main factors of actualization of these activities of students (social, socio-educational, socio-psychological, pedagogical, psychological) and revealed the essence of each of those. This publication submits a brief description of the principles, goals, objectives, contents, methods, means and forms of organization of educational work on extracurricular classes of students on academic subjects, it also stresses the importance of optimal selection of the content of the material, the choice of methods, means and forms of extracurricular work, integrating extracurricular and classroom work of students, individualization and differentiation of their education and training in extracurricular activities. The article shows the role of the teacher in the development of the student's individuality in extracurricular activities.